Application of resettable elements for electrical protection of solar batteries - Tonkoshkur, О. S.; Ivanchenko, О. V.; Nakashydze, L. V.; Mazurik, S. V. (Technology and design in electronic equipment, 2018)
The manifestation and formation of various defects in the process of exploitation in real photovoltaic cells and their compounds as well as their work in the regime of changing non-uniform illumination lead to the so-called series and parallel inconsistencies (differences of electrical characteristics) between separate cells and their groups. This results in local overheating and intensifying of degradation processes.In some cases temporary disconnection (isolation) of the corresponding elements of the solar batteries is more appropriate in order to increase their service life.In this work additional devices for insulation of overheating cells (and/or components) of solar batteries such as «PolySwith» resettable fuses are proposed to be used as a perspective solution of such problems. These structures are polymer composites with nanosized carbon fillers. Electrical resistance of such a fuse increases abruptly by several orders of magnitude when certain threshold temperature is reached, and when the temperature decreases the fuse returns to its initial high-conductivity state.This study investigates the possibilities of using the specified type of fuses for electrical insulation of «overheated» photovoltaic cells. Particular attention is paid to the research of the effect of fuses on the working of the solar batteries in the operating temperature range and their functional applicability in emergency situations associated with overheating. The studies were carried out using a model structure of several series of parallel connected photovoltaic cells and specified fuses. Attention is paid to the influence of such factors as the ambient temperature and the drift of the fuses resistance in the conducting state in the process their multiple switching.It has been established that such protection elements do not influence the work of solar batteries in operating temperature range and are functionally applicable for the electrical isolation of local regions and components of solar batteries with increased temperature.